2020
DOI: 10.3991/ijim.v14i14.14719
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using STEAM Approach on Developing Computational Thinking Skills among High School Students in Jordan

Abstract: The growing demand for combining digital technology with learning practices has surpassed the use of technology or learning how to use it into the process of enhancing learners’ intellectual levels and scaffolding their understanding by focusing on skills that include thought processes gathered in what is called computational thinking. On the other hand, educational challenges promote the search for new instructional tools and approaches. Consequently, learning shall be extended by superimposing science, techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…The utilization of digital technology in the learning process can improve student skills and knowledge. Similarly, Al-Haj Bedar & Al-Shboul [57] state that digital technology in the classroom helps students focus on the learning process. Al-Jarf's [58] reports that computerized mind maps can encourage creativity because they allow students to be more adept at generating and forming ideas that are complex to write about.…”
Section: Digital Mind Map (Dmm)mentioning
confidence: 99%
“…The utilization of digital technology in the learning process can improve student skills and knowledge. Similarly, Al-Haj Bedar & Al-Shboul [57] state that digital technology in the classroom helps students focus on the learning process. Al-Jarf's [58] reports that computerized mind maps can encourage creativity because they allow students to be more adept at generating and forming ideas that are complex to write about.…”
Section: Digital Mind Map (Dmm)mentioning
confidence: 99%
“…Adopting technology depends on the effectiveness of using this technology in education to improve information literacy. Previous research proved that developmentally appropriate technology stimulated student computational thinking concept fluency and the development of student interests in computing at the beginning period [15,21]. Other findings stated that applying educational application affected understanding the concept and knowledge, enhancing the learning process, and increasing student learning outcomes [22][23][24][25].…”
Section: Educational Application Designmentioning
confidence: 99%
“…Their collective findings reported that the application of technology in education could improve student anger management skills, enhance the teaching-learning process's effectiveness, increase academic achievement, and foster positive behavior [7][8][9][10][11][12][13]. Other studies presented that the application of technology can raise problem-solving capability, heighten computational thinking competency, upgrade writing ability, be adopted due to usefulness and easiness, and boost motivation [14][15][16][17][18][19]. The advantages of using technology in education in the cognitive and affective domain are seen in the current studies` interests.…”
Section: Introductionmentioning
confidence: 99%
“…The term grew out of the pioneering work of Papert and colleagues on design-based constructionist programming environments; where it refers to ways of algorithmically solving problems and to the acquisition of technological fluency [30]. Then, in 2006, Wing had broaden the CT concept by stating that CT is a basic skill for everyone and is relevant in all fields [31,63]. The skill of CT was initially adopted as the basic field of computer science in solving problems, designing systems and understanding human behaviors.…”
Section: Interactionmentioning
confidence: 99%